Ibrutinib enhances IL-17 response by modulating the function of bone marrow derived dendritic cells. (2nd January 2016) - Natarajan, Gayathri; Terrazas, Cesar; Oghumu, Steve; Varikuti, Sanjay; Dubovsky, Jason A; Byrd, John C; Satoskar, Abhay R
Abstract : Ibrutinib (PCI-32765) is an irreversible dual Btk/Itk inhibitor shown to be effective in treating several B cell malignancies. However, limited studies have been conducted to study the effect of this drug on myeloid cell function. Hence, we studied the effect of ibrutinib treatment on TLR-4 mediated activation of bone marrow derived dendritic cell culture (DCs). Upon ibrutinib treatment, LPS-treated DCs displayed lower synthesis of TNF-α and nitric oxide (NO) and higher induction of IL-6, TGF-β, IL-10 and IL-18. While ibrutinib dampened MHC-II and CD86 expression on DCs, CD80 expression was upregulated. Further, ibrutinib-treated DCs promoted T cell proliferation and enhanced IL-17 production upon co-culture with nylon wool enriched T cells. Taken together, our results indicate that ibrutinib modulates TLR-4 mediated DC activation to promote an IL-17 response. We describe a novel mode of action for ibrutinib on DCs which should be explored to treat other forms of cancer besides B cell malignancies.